Ancestry, Diversity & Finance: Evidence from Transition Economies - Akos Dombi; Theocharis Grigoriadis (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2017)
In this paper, we analyze the growth effects of historical and biological ancestry, diversity and financial development in transition economies. We show that the common indicators of ethnolinguistic fractionalization, state history and genetic distance yield significant results and to some extent transform the impact of finance on growth in East-Central Europe and the former Soviet Union. Deep ethnolinguistic cleavages produce insignificant results, whereas at intermediate and lower levels of aggregation diversity is likely to significantly improve the effect of finance on growth. Similarly to finer ethnolinguistic cleavages, genetic distance from the United States also favorably increases the relevance of financial development for growth. However, state history as a proxy for long-run ancestral exposure to institutions, political organization and centralization reinforces the negative growth effect of financial development. We argue that financial development is inclined to resolve problems arising from coordination failures and absence of trust in diverse societies by easing liquidity constraints and offering incentives for entrepreneurship to minority groups. In contrast, long state history is likely to generate extractive institutions that facilitate the provision of soft budget constraints. Genetic distance from the United States induces higher reliance on continental rather than Anglo-Saxon financing practices, and therefore increases dependence on banks rather than bonds or equity for external liquidity purposes.
Keywords: G21; O15; O43; P26; P51; Z10; 330; financial development; economic growth; state history; ethnolinguistic diversity; genetic distance; transition economies